Resistance spot welded joint and manufacturing method thereof

By forming a three-layer hardness structure on the surface of high-strength steel plates, the problem of LME cracking during resistance spot welding is solved, and the stability of welding strength and the suppression of zinc embedding is achieved.

JP7656203B2Active Publication Date: 2025-04-03NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021198001
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-06
Publication Date
2025-04-03
Estimated Expiration
2041-12-06

AI Technical Summary

Technical Problem

During the resistance spot welding process of high-strength steel plates, liquid zinc embedded brittle deformation (LME cracking) is prone to liquid zinc embedded brittle deformation (LME cracking), resulting in the welding strength being unavailable and difficult to suppress.

Method used

By forming a three-layer hardness structure on the surface of the high-strength steel plate, the hardness of the first and third layers is higher, while the hardness of the second layer is lower than that of the first and third layers, the strain introduced during the welding process is absorbed, thereby inhibiting the embedment of zinc.

Benefits of technology

It effectively suppresses the occurrence of LME cracking, ensures the stability of welding strength, and improves the safety of high-strength steel plates during resistance spot welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656203000003
    Figure 0007656203000003
  • Figure 0007656203000004
    Figure 0007656203000004
  • Figure 0007656203000005
    Figure 0007656203000005
Patent Text Reader

Abstract

To provide a resistance spot-weld joint including a high strength steel sheet and capable of inhibiting LME crack at spot welding, and a production method for the above joint.SOLUTION: A resistance spot-weld joint comprises a plurality of overlapped steel sheets, nuggets joining the steel sheets, and a weld zone having a corona bond formed in the surround of nuggets and a heat-affected zone. At least one among the plurality of steel sheets is a high strength steel sheet having the tensile strength of 980 MPa or more, and that high strength steel sheet or the sheet adjacent to the high strength one is galvanized. The joint is characterized in that in a base material surface on which the base material of the sheet contacts a galvanized plating, the hardness in a depth region of 10-60 μm from the base material surface is lower than the hardness in the depth region of 1-10 μm from the above surface and that in the depth region of 60 μm or more from the above surface. The production method for the joint is also disclosed.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resistance spot welded joint and a method for manufacturing the same. [Background technology]

[0002] In recent years, the automobile industry has been seeking to reduce the weight of vehicle bodies in order to improve fuel efficiency. In order to achieve both a lighter vehicle body and crashworthiness, one effective method is to increase the strength of the steel plates used in the frame components, etc., and against this background, the development of high-strength steel plates has been progressing.

[0003] High-strength steel sheets used in automobiles and other applications require excellent weldability. Resistance spot welding is mainly used in processes such as assembling automobile bodies and installing parts. In particular, resistance spot welding between galvanized steel sheets or between galvanized and non-galvanized steel sheets requires the prevention of liquid metal embrittlement (LME) cracking. This phenomenon occurs when zinc, which has been liquefied by the welding heat input, penetrates into the steel sheet along the grain boundary, and tensile stress generated by welding acts on the part of the steel sheet. If such LME cracking occurs in spot welding using high-strength steel sheets, the strength of the welded joint cannot be ensured, and this may hinder the use of the high-strength steel sheets.

[0004] In relation to this, Patent Document 1 describes a joint structure formed by resistance welding a plurality of overlapping steel sheets, in which at least one of the plurality of steel sheets is a high-tensile steel sheet having a chemical composition with a carbon equivalent Ceq of 0.53% or more and a tensile strength of 590 MPa or more, and the high-tensile steel sheet has a decarburized layer between the base material and a zinc-based plating layer formed on at least one of the overlapping surface side and the welding electrode side, or on the overlapping surface adjacent to the zinc-based plating layer of the overlapping zinc-based plated steel sheet, and the decarburized layer has a thickness of 5 μm or more and 200 μm or less. Furthermore, Patent Document 1 also describes that the presence of a decarburized layer between the zinc-based plating layer and the base metal, which has a higher A3 point than the base metal and is less susceptible to austenite transformation (reverse transformation), makes it difficult for the surface layer of the HAZ (heat-affected zone) to become a coarse austenite structure during welding, and as a result, it suppresses embrittlement caused by zinc that disperses from the molten zinc in the zinc-based plating layer during welding and penetrates into the grain boundaries of the HAZ, making it possible to prevent cracking even if tensile stress is applied in the presence of molten zinc.

[0005] Patent Document 2 describes a spot-welded component in which a plurality of steel sheets are spot-welded, at least one of which is a high-strength cold-rolled steel sheet having a tensile strength of 780 MPa or more and no plating layer on its surface, at least one of which is a zinc-based plated steel sheet having a zinc-based plating layer on its surface, and the surface layer Zn concentration inside the corona bond of the spot weld is 1 mass % or more and less than 25 mass %. Patent Document 2 also describes that by controlling the surface layer Zn concentration inside the corona bond of the spot weld, it is possible to suppress LME cracking (LME cracking that occurs when the mating material to which the high-strength steel sheet is welded has a zinc-based plating layer) in the weld, even though the spot-welded component includes a high-strength cold-rolled steel sheet.

[0006] Patent Document 3 describes a high-strength steel sheet having a steel structure with a predetermined composition, an area ratio of ferrite of 15% to 55%, an area ratio of hard phase of 40% to 85%, a volume ratio of retained austenite of 4% to 20%, a carbon concentration in the retained austenite of 0.55% to 1.10%, a diffusible hydrogen content in the steel sheet of 0.80 mass ppm or less, a surface layer softening thickness of 5 μm to 150 μm, and a correspondence grain boundary frequency of the steel sheet surface layer after a high-temperature tensile test of 0.45 or less, and a tensile strength of 980 MPa or more. Patent Document 3 also describes that a high-strength steel sheet with excellent LME resistance can be realized by controlling the correspondence grain boundary frequency of the steel sheet surface layer after a high-temperature tensile test to 0.45 or less and the surface layer softening thickness to 5 μm to 150 μm or less. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2020-082102 A [Patent Document 2] JP 2020-179413 A [Patent Document 3] International Publication No. 2020 / 184154 Summary of the Invention [Problem to be solved by the invention]

[0008] In general, it is known that LME cracking occurs more significantly when steel sheets having a relatively high strength are spot welded, and the higher the strength of the steel sheet, the higher the susceptibility to LME cracking tends to be. On the other hand, the automobile industry and other industries are also demanding further weight reduction of steel sheets, and in order to achieve such weight reduction, it is necessary to make the steel sheets stronger than ever before. Therefore, even when spot welding is performed using steel sheets that have been strengthened to the same extent or more than conventional ones, there is a continuing need to be able to solve the problem of LME cracking, and there is still room for improvement in this respect even in conventional welded components and high-strength steel sheets.

[0009] Therefore, an object of the present invention is to provide a resistance spot welded joint including a high-strength steel plate with a novel configuration, which can suppress the occurrence of LME cracking during spot welding, and a manufacturing method thereof. [Means for solving the problem]

[0010] The present inventors have investigated a method for suppressing or reducing the occurrence of LME cracking, focusing particularly on high-strength steel sheets used in resistance spot-welded joints. As a result, the present inventors have found that when the depth region from the base metal surface of a high-strength steel sheet in contact with a zinc-based coating is divided into a first depth region of 1 to 10 μm, a second depth region of 10 to 60 μm, and a third depth region of 60 μm or more, by making the hardness of the second depth region lower than the hardness of the first and third depth regions to form a three-layer structure, the strain induced in the high-strength steel sheet by deformation during spot welding can be borne by a layer (second depth region) with a relatively low hardness, and thus an excessive increase in strain in the outermost layer (first depth region) can be suppressed, thereby suppressing the penetration of molten zinc into the steel sheet, and have completed the present invention.

[0011] The present invention, which has achieved the above object, is as follows. (1) A plurality of overlapping steel plates; a nugget for joining the steel plates, and a welded portion having a corona bond and a heat-affected zone formed around the nugget; A resistance spot welded joint comprising: At least one of the plurality of steel plates is a high-strength steel plate having a tensile strength of 980 MPa or more; The high-strength steel sheet has a zinc-based coating, or a steel sheet adjacent to the high-strength steel sheet has a zinc-based coating, On a surface of the base material of the high strength steel plate where the base material is in contact with the zinc-based plating, A resistance spot welded joint, characterized in that the hardness of a region 10 to 60 μm deep from the base metal surface is lower than the hardness of a region 1 to 10 μm deep from the base metal surface and the hardness of a region 60 μm or more deep from the base metal surface. (2) the surface of the base material of the high-strength steel plate in contact with the zinc-based plating is located at the overlapping interface of multiple overlapping steel plates; The base material has a surface area of ​​1 to 10 μm deep and has a diameter of 10 to 200 precipitates / μm that are less than 0.1 μm. 2 exists at a number density of The resistance spot welded joint according to (1) above, characterized in that the amount of solute C in a region at a depth of 10 to 60 μm from the surface of the base material is less than 0.20 mass %. (3) The resistance spot welded joint according to (2) above, characterized in that an amount of η-phase in the zinc-based plating within the corona bond of the overlapping surfaces of the multiple steel sheets where the surface of the base material of the high-strength steel sheet in contact with the zinc-based plating is located is 20 area % or less. (4) the surface of the base material of the high-strength steel plate in contact with the zinc-based plating is located on the outermost surface of the multiple overlapping steel plates; The base material has a surface area of ​​1 to 10 μm deep and has a diameter of 10 to 200 precipitates / μm that are less than 0.1 μm. 2 exists at a number density of The resistance spot welded joint according to (1) above, characterized in that the amount of solute C in a region at a depth of 10 to 60 μm from the surface of the base material is less than 0.20 mass %. (5) The resistance spot welded joint according to (4) above, characterized in that an amount of η phase in the zinc-based plating in a shoulder portion of a weld on the outermost surfaces of the plurality of steel plates where a base metal surface of the high-strength steel plate contacts the zinc-based plating is located is 20 area % or less. (6) pressing the stacked steel sheets using a pair of opposing electrodes; forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; continuously decreasing the current value between the electrodes to 0 while maintaining pressure on the plurality of steel plates; The method for producing a resistance spot welded joint according to any one of (1) to (5) above, comprising: (7) pressing the stacked steel sheets using a pair of opposing electrodes; forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; reducing the current value between the electrodes to 0 while maintaining pressure on the steel plates; The current value between the electrodes at the time when the formation of the nugget is completed is defined as I, and 1 / 2 of the total sheet thickness of the steel sheet in mm is defined as tm. The method for manufacturing a resistance spot welded joint according to any one of the above (1) to (5), characterized in that when the current value between the electrodes is reduced to 0 or for less than 0.04 seconds after it is reduced to 0, the current value between the electrodes is held at a constant value of 0.12 × tm or more per sec within a range of 0.9 × I to 0.3 × I. (8) pressing the stacked steel sheets using a pair of opposing electrodes; A step of preheating the steel sheets by applying a pre-current between the electrodes while pressing the plurality of steel sheets; forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; The method for producing a resistance spot welded joint according to any one of (1) to (5) above, comprising: (9) pressing the stacked steel sheets using a pair of opposing electrodes; forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; Reducing the current value between the electrodes to 0 while maintaining pressure on the steel plates; a step of maintaining the applied pressure at 0.8×P or more for 0.2 sec to 0.4 sec with the current value between the electrodes at 0; wherein P is a pressing force at a time when formation of the nugget is completed. Effect of the Invention

[0012] According to the present invention, it is possible to provide a resistance spot welded joint including a high-strength steel plate, which is capable of suppressing the occurrence of LME cracking during spot welding, and a manufacturing method thereof. [Brief description of the drawings]

[0013] [Figure 1] 1A and 1B are diagrams showing a schematic diagram of a method for manufacturing a resistance spot-welded joint according to an embodiment of the present invention, in which FIG. 1A shows a state before manufacturing the resistance spot-welded joint, and FIG. 1B shows a state after resistance spot welding has been performed. [Diagram 2] FIG. 1 is a schematic diagram of a resistance spot welded joint according to a preferred embodiment of the present invention when two steel plates are overlapped. [Diagram 3] FIG. 1 is a schematic diagram of a resistance spot welded joint according to a preferred embodiment of the present invention in the case where three steel plates are overlapped. [Figure 4] FIG. 2 is a diagram showing a schematic diagram of a change in current over time in manufacturing method 1. [Diagram 5] FIG. 13 is a diagram showing a schematic diagram of changes in current and applied pressure over time in a preferred embodiment of the manufacturing method 1. [Figure 6] 13 is a diagram showing a schematic diagram of a change in current over time in manufacturing method 2. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <Resistance spot welded joint> The resistance spot welded joint according to an embodiment of the present invention is A plurality of overlapping steel plates; a nugget for joining the steel plates, and a welded portion having a corona bond and a heat-affected zone formed around the nugget; Equipped with At least one of the plurality of steel plates is a high-strength steel plate having a tensile strength of 980 MPa or more; The high-strength steel sheet has a zinc-based coating, or a steel sheet adjacent to the high-strength steel sheet has a zinc-based coating, On a surface of the base material of the high strength steel plate where the base material is in contact with the zinc-based plating, The hardness of a region 10 to 60 μm deep from the base material surface is lower than the hardness of a region 1 to 10 μm deep from the base material surface and the hardness of a region 60 μm or deeper from the base material surface.

[0015] As mentioned above, LME cracking occurs more prominently when steel plates with relatively high strength are spot welded, and it is known that the higher the strength of the steel plate, the higher the susceptibility to LME cracking. When two or more steel plates, including at least one high-strength steel plate, are stacked and spot welded to create a joint, if the degree of disturbance such as the impact angle (the angle between the axial direction of the electrode and the direction perpendicular to the surface of the steel plate) or the gap between the plates increases, LME cracking may occur inside or just outside the pressure joint (corona bond) formed on the outside of the weld metal (nugget), or on the surface of the electrode side. LME cracking occurs when tensile stress is applied to zinc in a molten state or at a temperature close to its melting point. The magnitude of the tensile stress is affected by many factors, such as the pressure applied by the electrode, the expansion and contraction of the weld, and the springback when the electrode is released. Since the occurrence of LME cracking is thus affected by the magnitude of temperature and tensile stress, it is important to suppress the increase in temperature and tensile stress in order to suppress LME cracking. However, in order to obtain a nugget diameter sufficient for joining, it is necessary to increase the welding heat input and increase the temperature. For this reason, it may be difficult to suppress the temperature increase. Therefore, in order to address LME cracking by suppressing or reducing the stress applied during spot welding, the inventors focused on high-strength steel plates used in resistance spot-welded joints and conducted research from the perspective of making the configuration of the high-strength steel plates more appropriate.

[0016] More specifically, the inventors first found that the occurrence of LME cracking is greatly influenced by the "strain" introduced into the surface layer of a high-strength steel sheet due to the stress applied during spot welding. For example, it was found that even with the same current cycle (thermal history), the occurrence of LME cracking becomes more pronounced when spot welding is performed to increase the amount of plastic deformation of the steel sheet. The reason why LME cracking is more likely to occur with an increase in "strain" is thought to be that as the strain in the surface layer of the steel sheet increases, molten zinc is more likely to penetrate from the surface layer of the steel sheet to the inside. Therefore, by preventing an increase in strain in the surface layer of the steel sheet, it is possible to suppress the occurrence of LME cracking even when a welded joint is manufactured by spot welding a high-strength steel sheet. The inventors found that it is effective to provide a hardness difference in the thickness direction of the surface layer of the steel sheet as a means for preventing an increase in strain in the surface layer of the steel sheet. Specifically, when the depth from the base metal surface of the high-strength steel sheet in contact with the zinc-based plating is divided into a first depth region of 1 to 10 μm, a second depth region of 10 to 60 μm, and a third depth region of 60 μm or more, the hardness of the second depth region is controlled to be lower than the hardness of the first and third depth regions. By making the depth region from the base metal surface in the plate thickness direction of the high-strength steel sheet into a three-layer structure in which the hardness of the second depth region is controlled to be lower than the hardness of the first and third depth regions, the strain induced in the surface layer of the high-strength steel sheet by deformation during spot welding can be borne by a layer (second depth region) with a relatively low hardness, thereby making it possible to suppress an increase in stress in the outermost layer (first depth region) and therefore an excessive increase in strain. Therefore, by using a high-strength steel plate having a depth region consisting of the above-mentioned three-layer structure, it is possible to suppress the penetration of molten zinc into the steel plate during spot welding, thereby significantly suppressing or preventing the occurrence of LME cracking, and as a result, it is possible to obtain a resistance spot welded joint with sound joint strength.

[0017] Hereinafter, the resistance spot welded joint according to the embodiment of the present invention will be described in more detail with reference to the drawings. However, these descriptions are intended to merely illustrate preferred embodiments of the present invention, and are not intended to limit the present invention to such specific embodiments.

[0018] FIG. 1 is a diagram showing a schematic diagram of a resistance spot welded joint according to an embodiment of the present invention, in which FIG. 1(a) shows a state before the resistance spot welded joint is manufactured, and FIG. 1(b) shows a state after the resistance spot welding is performed. Referring to FIG. 1(a), a high-strength steel sheet 11 having a tensile strength of 980 MPa or more has a zinc-based plating 12 on both surfaces thereof, and the high-strength steel sheet 11 is overlapped with a steel sheet 11' not having a zinc-based plating in a state in which the overlapping surface 15 is adjacent to each other. Next, as shown in FIG. 1(b), the two overlapped steel sheets are pressed using a pair of electrodes A facing each other. Then, a nugget 13 and a corona bond 14 are formed by passing a current between the electrodes A while pressing the two steel sheets, and finally, a resistance spot welded joint 1 is manufactured, which includes the two overlapped steel sheets 11 and 11', a nugget 13 that joins these steel sheets, and a welded portion 17 having a corona bond 14 and a heat-affected zone 16 formed around the nugget 13. The shape and structure of the nugget 13 are not particularly limited, but for example, the nugget 13 has a single structure or a double structure, and preferably has a single structure. In resistance spot welding, there are cases where re-energization is performed after a short cooling time (non-energization time) that is long enough for the nugget to solidify. In such a case, two-stage cooling is performed, namely, cooling during cooling and cooling after re-energization, so the nugget has a double structure. Since the resistance spot welded joint 1 according to the embodiment of the present invention can be manufactured regardless of whether or not such a cooling time is performed, the nugget 13 can have both a single structure and a double structure, but according to a preferred embodiment, the nugget 13 of the resistance spot welded joint 1 has a single structure.

[0019] In Fig. 1(b), since the high-strength steel sheet 11 has the zinc-based coating 12 on both surfaces thereof, the surface of the base material of the high-strength steel sheet 11 that is in contact with the zinc-based coating 12 is located on both the overlapping surface 15 and the opposite side, i.e., the outermost surface (electrode A side) of the two overlapped steel sheets. In this case, due to strain introduced into the high-strength steel sheet 11 by deformation during spot welding, LME cracks may occur on both sides of the high-strength steel sheet 11, i.e., on both the overlapping surface 15 side and the electrode A side. More specifically, LME cracks may occur, for example, inside or immediately outside the corona bond 14 of the overlapping surface 15, or in the heat-affected zone of the surface on the electrode A side (for example, the weld shoulder 18 corresponding to the outer edge of the electrode impression or its periphery). However, according to an embodiment of the present invention, the depth region from the base metal surface of the high-strength steel plate 11 has a three-layer structure in which the hardness of the second depth region is controlled to be lower than the hardness of the first and third depth regions as described above, making it possible for the second depth region to absorb more of the strain introduced into the steel plate due to deformation during spot welding than the first depth region, and as a result, it is possible to suppress the occurrence of LME cracks on both the overlap surface 15 side and the electrode A side of the high-strength steel plate 11.

[0020] 1(a) and (b), for ease of understanding, a welded joint in which only two steel sheets are overlapped and only one of the high-strength steel sheets 11 is coated with a zinc-based plating 12 has been described. However, the resistance spot welded joint 1 according to the embodiment of the present invention is not necessarily limited to such a welded joint, and may include welded joints having various configurations in which the base material of the high-strength steel sheet 11 is in contact with the zinc-based plating 12. For example, when a high-strength steel sheet 11 having a tensile strength of 980 MPa or more has a zinc-based plating 12, it is sufficient that at least one of two or more steel sheets, for example, three steel sheets, has a zinc-based plating 12 on one or both surfaces, and the other steel sheets may or may not be high-strength steel sheets 11. Moreover, these other steel sheets may or may not have a zinc-based plating 12. 1(a) and (b) show the case where the high-strength steel sheet 11 has the zinc-based coating 12 on both surfaces, but for example, the high-strength steel sheet 11 may have the zinc-based coating 12 only on the overlap surface 15 side. In this case, there is a possibility that LME cracks may occur inside the corona bond 14 of the overlap surface 15 or just outside thereof. However, according to the embodiment of the present invention, since the depth region from the base metal surface of the high-strength steel sheet 11 having the zinc-based coating 12 has the above-mentioned three-layer structure, the second depth region reliably absorbs the strain introduced into the steel sheet due to deformation during spot welding, and therefore it is possible to reliably suppress the occurrence of LME cracks inside the corona bond 14 on the overlap surface 15 side of the high-strength steel sheet 11 or just outside thereof. Similarly, when the high-strength steel sheet 11 has the zinc-based plating 12 only on the electrode A side, there is usually a possibility that LME cracking may occur in the heat-affected zone on the surface of the electrode A side, etc.; however, according to an embodiment of the present invention, the depth region from the base metal surface of the high-strength steel sheet 11 having the zinc-based plating 12 has the above-mentioned three-layer structure, so that the second depth region reliably absorbs the strain introduced into the steel sheet due to deformation during spot welding, thereby reliably suppressing the occurrence of LME cracking in the heat-affected zone on the surface of the electrode A side of the high-strength steel sheet 11.

[0021] On the other hand, when the high-strength steel sheet 11 does not have the zinc-based coating 12, it is sufficient that the steel sheet to be overlapped with the high-strength steel sheet 11 among one or more other steel sheets has the zinc-based coating 12 at least on the overlapping surface 15 side. When an additional steel sheet is included in addition to these two steel sheets, the additional steel sheet may or may not be the high-strength steel sheet 11, and may or may not have the zinc-based coating 12. For example, when a set of three steel sheets is spot welded, in which a steel sheet 11' having a relatively low tensile strength and having zinc-based coating 12 on both surfaces is overlapped with a high-strength steel sheet 11 not having the zinc-based coating 12 on both sides, LME cracks may occur inside the corona bond 14 on the overlapping surface 15 side on both sides of the steel sheet 11'. However, by using high-strength steel plates having a depth region consisting of the above-mentioned three-layer structure as the other two high-strength steel plates 11, the second depth regions in these high-strength steel plates can reliably absorb the strain introduced into the steel plates due to deformation during spot welding, thereby reliably suppressing the occurrence of LME cracks, for example, inside the corona bond 14 on the overlap surface 15 side of the high-strength steel plates 11.

[0022] FIG. 2 is a schematic diagram of a resistance spot welded joint according to a preferred embodiment of the present invention when two steel sheets are overlapped. In both of FIG. 2(a) and (b), the high-strength steel sheet 11 has a zinc-based coating 12 on both surfaces, and FIG. 2(a) has a configuration similar to that of FIG. 1, whereas FIG. 2(b) has two high-strength steel sheets 11 having zinc-based coating 12 overlapped adjacently at the overlapping surface 15. In FIG. 2(a), as described in relation to FIG. 1, two regions of one high-strength steel sheet 11, the overlapping surface 15 side and the electrode A side, are exposed to the risk of LME cracking. On the other hand, in FIG. 2(b), a total of three regions, the overlapping surface 15 side and the electrode side of each high-strength steel sheet 11, are exposed to the risk of LME cracking. However, by forming the depth region from the base metal surface of the high-strength steel plate 11 into a three-layer structure in which the hardness of the second depth region of 10 to 60 μm is lower than the hardness of the first depth region of 1 to 10 μm and the third depth region of 60 μm or more as described above, the risk of LME cracking can be avoided or reliably suppressed in all of the above regions. In addition, in FIG. 2(b), only one of the two high-strength steel plates 11 may be a steel plate having the above three-layer structure, and such an embodiment is also included in the present invention. In this case, although there is a possibility that the joint strength may be somewhat lower than that in the case of a resistance spot welded joint in which both high-strength steel plates 11 have the above three-layer structure, the number and positions of the high-strength steel plates having the above three-layer structure may be appropriately determined in consideration of the desired joint strength, etc.

[0023] FIG. 3 is a schematic diagram of a resistance spot welded joint according to a preferred embodiment of the present invention in the case where three steel sheets are overlapped. In all of the embodiments in FIG. 3(a) to (e), the high-strength steel sheet 11 has a zinc-based coating 12 on both surfaces. In this case, the entire base metal surface of the high-strength steel sheet 11 is in contact with the zinc-based coating 12. For this reason, in FIG. 3(a) to (e), all regions on the overlapping surface 15 side and the electrode side on which the high-strength steel sheet 11 is placed are exposed to the risk of LME cracking. However, by making the depth region from the base metal surface of the high-strength steel sheet 11 into a three-layer structure in which the hardness of the second depth region of 10 to 60 μm is lower than the hardness of the first depth region of 1 to 10 μm and the third depth region of 60 μm or more as described above, the risk of LME cracking can be avoided or reliably suppressed in all of the above regions. In addition, in FIG. 3(c) to (e), only one of the multiple high-strength steel sheets 11 may be a steel sheet having the above three-layer structure, and such an embodiment is also included in the present invention. In this case, although there is a possibility that the joint strength will be somewhat lower than in the case of a resistance spot welded joint in which all of the high-strength steel plates 11 have the above-mentioned three-layer structure, the number and positions of the high-strength steel plates having the above-mentioned three-layer structure may be appropriately determined taking into account the desired joint strength, etc.

[0024] In Fig. 3(a) to (e), a case where all the high-strength steel sheets 11 have the zinc-based coating 12 on both surfaces has been described for ease of understanding. However, the resistance spot welded joint 1 according to the embodiment of the present invention is not necessarily limited to such a welded joint, and may include welded joints having various configurations in which the base material of the high-strength steel sheet 11 is in contact with the zinc-based coating 12. For example, when the high-strength steel sheet 11 has the zinc-based coating 12, it is sufficient that at least one high-strength steel sheet 11 has the zinc-based coating 12 on one or both surfaces, and the other steel sheets may or may not be the high-strength steel sheet 11. In addition, these other steel sheets may or may not have the zinc-based coating 12. On the other hand, when the high-strength steel sheet 11 does not have the zinc-based coating 12, it is sufficient that the steel sheet overlapping the high-strength steel sheet 11 among the two other steel sheets has the zinc-based coating 12 at least on the overlapping surface 15 side. The remaining steel plate may or may not be a high-strength steel plate 11, and may or may not have a zinc-based coating 12. Hereinafter, the high-strength steel plate used in the resistance spot welded joint according to the embodiment of the present invention will be described in more detail.

[0025] [High strength steel plate] The high-strength steel sheet according to the embodiment of the present invention may be any material having a tensile strength of 980 MPa or more, and having a three-layer structure in which the hardness of the second depth region (depth region of 10 to 60 μm from the base material surface) in the depth region from the base material surface in contact with the zinc-based plating is controlled to be lower than the hardness of the first and third depth regions (depth regions of 1 to 10 μm and 60 μm or more from the base material surface). In general, the higher the strength of the steel sheet, the higher the susceptibility to LME cracking tends to be, and this tendency is particularly strong when the tensile strength is 980 MPa or more. Therefore, by applying the above three-layer structure to a high-strength steel sheet having a tensile strength of 980 MPa or more, the effect of suppressing LME cracking becomes particularly remarkable. For example, the tensile strength may be 1080 MPa or more, 1180 MPa or more, or 1200 MPa or more. The upper limit is not particularly limited, but the tensile strength may be, for example, 2300 MPa or less, 2000 MPa or less, 1800 MPa or less, or 1500 MPa or less. The tensile strength is measured by taking a JIS No. 5 test piece so that the longitudinal direction of the test piece is parallel to the rolling direction perpendicular to the steel plate, and conducting a tensile test in accordance with JIS Z 2241:2011.

[0026] The hardness of the second depth region is not particularly limited as long as it is lower than the hardness of the first and third depth regions. Here, in the present invention, the hardness of the second depth region (depth region of 10 to 60 μm from the base material surface) refers to the average Vickers hardness of the second depth region. Therefore, in the present invention, "the hardness of the second depth region (depth region of 10 to 60 μm from the base material surface) is lower than the hardness of the first and third depth regions (depth regions of 1 to 10 μm and 60 μm or more from the base material surface)" means that the average Vickers hardness of the second depth region is lower than the average Vickers hardness of the first and third depth regions. For example, the average Vickers hardness of the second depth region may be 0.98 times or less the average Vickers hardness of the first and / or third depth regions. From the viewpoint of suppressing an increase in strain occurring in the first depth region, it is preferable that the average Vickers hardness of the second depth region is relatively lower. Therefore, the average Vickers hardness of the second depth region is preferably 0.95 times or less, more preferably 0.92 times or less, and most preferably 0.90 times or less, the average Vickers hardness of the first and / or third depth region. Although there is no particular lower limit, for example, the average Vickers hardness of the second depth region may be 0.60 times or more or 0.70 times or more the average Vickers hardness of the first and / or third depth region.

[0027] In the present invention, the "hardness of the first depth region", the "hardness of the second depth region" and the "hardness of the third depth region" are determined as follows by performing a Vickers hardness test in accordance with JIS Z 2244-1:2020. First, the Vickers hardness is measured at three points at 3 μm intervals in the plate thickness direction from a depth position of 2 μm from the base material surface in the outer region of the heat-affected zone not affected by heat of the high-strength steel plate with an indentation load of 20 g, and the average value is determined as the hardness of the first depth region. Next, the Vickers hardness is measured at six points at 10 μm intervals in the plate thickness direction from a depth position of 10 μm from the base material surface with an indentation load of 20 g, and the average value is determined as the hardness of the second depth region. Finally, the Vickers hardness is measured at five points at 100 μm intervals in the plate thickness direction from a depth position of 60 μm from the base material surface with an indentation load of 20 g, and the average value is determined as the hardness of the third depth region.

[0028] [Preferred embodiment of high strength steel plate] Below, preferred configurations for realizing a high-strength steel plate having a depth region consisting of a three-layer structure in which the hardness of the second depth region is controlled to be lower than the hardness of the first and third depth regions will be described. However, these descriptions are intended to be merely illustrative of preferred embodiments of the present invention, and are not intended to limit the present invention to such specific embodiments.

[0029] [The number density of precipitates having a diameter of less than 0.1 μm in a first depth region of 1 to 10 μm from the base material surface is 10 to 200 pieces / μm 2 ] In the case of high-strength steel plate, precipitates with a diameter of less than 0.1 μm are formed at 10 to 200 particles / μm in a first depth region of 1 to 10 μm from the base material surface. 2 It is preferable that the fine precipitates are present at a number density of 10 particles / μm. The presence of a large number of such fine precipitates refines the steel sheet structure in the first depth region, and as a result, the strength and hardness of the steel sheet in the first depth region can be made higher than those of the second depth region. This makes it possible to increase the deformation resistance of the steel sheet in the first depth region at the stage when it is heated to a high temperature during spot welding. Therefore, when an electrode is pressed against the steel sheet to pass a current during spot welding and a load is applied while the steel sheet is held at a high temperature, it is possible to suppress an increase in plastic strain in the first depth region of the steel sheet. From the viewpoint of increasing the deformation resistance during welding and suppressing LME cracking, the lower limit of the number density of precipitates having a diameter of less than 0.1 μm in the first depth region is set to 10 particles / μm. 2 More preferably, it should be 15 / μm or more. 2 More than 30 pieces / μm 2 More than 60 pieces / μm 2 More than 90 pieces / μm 2 On the other hand, if the number density of precipitates is too high, the presence of oxides at high density increases the electrical resistance of the steel sheet surface, increasing the amount of heat generated in the steel sheet surface layer, which may result in reduced weldability. For this reason, the number density of precipitates with a diameter of less than 0.1 μm in the first depth region is set to 200 pieces / μm 2It is preferable that the number of particles is 150 or less per μm. 2 Less than or 120 pieces / μm 2 The above precipitates may be any precipitates, but are not particularly limited thereto, and include, for example, Ti precipitates and W precipitates, and more specifically, Ti oxides and Ti carbides. The precipitates in the present invention are, for example, oxide or carbide particles, such as TiO, TiO2, Ti2O3, Ti3O5, and TiC.

[0030] [Method for measuring the number density of precipitates with a diameter of less than 0.1 μm in a first depth region of 1 to 10 μm from the base material surface] The diameter and number density of precipitates in the first depth region of 1 to 10 μm from the base material surface are determined by observing the structure of the steel cross section. The dispersion state of precipitates does not change in the observation direction of RD (rolling direction of the steel sheet) or TD (width direction of the steel sheet), so the structure can be observed in a plane perpendicular to the ND plane (base material surface). Samples are taken from the base material surface in the outer region of the heat-affected zone that is not affected by heat of the high-strength steel sheet. A sample for observation is cut out from the surface of the material that has been pre-treated by mechanically polishing the polished surface to a mirror finish using a focused ion beam (FIB) processing device, and the precipitates are identified and the diameter of each precipitate particle is determined by observing the precipitates using a field emission transmission electron microscope (FE-TEM) at a magnification of 50,000 times and analyzing the composition using an energy dispersive X-ray detector (EDX). The field of view for observation is 10 μm in the plate thickness direction, and when the plate thickness direction is the height direction in the observation image, which is a two-dimensional image, the length in the horizontal direction perpendicular to this height direction is 5 μm, that is, 50 μm 2The total number of precipitates with a diameter of less than 0.1 μm obtained by observation and composition analysis is divided by this area to obtain the number of precipitates per unit area (number density). There is no limit to the area of ​​the sample used for observation as long as the dimensions include this area, but it is desirable that the height of the sample is more than 60 μm in order to measure the amount of dissolved C in the surface layer, which will be described later. Furthermore, since the total number of carbides measured may change if the thickness of the sample changes, the thickness of the sample is set to 10 to 30 nm, and it is preferable to prepare the sample with a thickness of 15 to 25 nm.

[0031] [The amount of solute C in the second depth region of 10 to 60 μm from the base material surface is less than 0.20 mass%] In general, the amount of solute C affects the strength of steel, and the greater the amount of solute C, the greater the deformation resistance. On the other hand, the smaller the amount of solute C, the lower the strength of the steel, i.e., the steel becomes relatively soft. As mentioned above, in order to suppress the occurrence of LME cracking during spot welding, it is important to prevent an increase in strain in the surface layer of the steel sheet. Therefore, in the high-strength steel sheet according to the embodiment of the present invention, the amount of solute C in the second depth region 10 to 60 μm from the base metal surface is reduced, preferably compared to the C content of the entire steel sheet, so that the strength and hardness of the second depth region can be reduced compared to the first depth region. As a result, the second depth region can absorb more strain introduced into the steel sheet by hot deformation during spot welding than the first depth region, making it possible to suppress LME cracking. If the amount of solute C in the second depth region is too high, the strength and hardness of the steel in the second depth region increases, and the second depth region may not be able to sufficiently suppress the increase in strain occurring in the first depth region. Therefore, the amount of solute C in the second depth region is preferably less than 0.20% by mass, and may be 0.19% by mass or less, 0.18% by mass or less, or 0.17% by mass or less. The lower limit is not particularly limited and may be 0% by mass. For example, the amount of solute C may be 0.01% by mass or more, 0.05% by mass or more, or 0.10% by mass or more.

[0032] [Method for measuring the amount of dissolved C in the second depth region of 10 to 60 μm from the base material surface] The amount of solute C in the second depth region is obtained by cutting out an evaluation sample in the same manner as described in relation to the method for measuring the number density of precipitates in the first depth region, and observing it with FE-TEM and analyzing it with EDX. In order to obtain the composition of the second depth region 10 to 60 μm from the base material surface, the height of the sample must be at least 60 μm. When C exists as precipitates rather than as solute C, its existence form is limited to two types: non-metallic inclusions including oxides and carbides. The concentration of C in non-metallic inclusions including oxides and carbides is more than twice the average composition value of the steel sheet. For this reason, in the map analysis values ​​by FE-TEM and EDX in the second depth region 10 to 60 μm from the base material surface, the region that is twice or less the average composition of the steel sheet is regarded as the steel matrix, and the average amount of C in that region is regarded as the amount of solute C.

[0033] The C content in the chemical composition of the entire high-strength steel plate is preferably 0.20 to 0.40 mass%. In the high-strength steel plate according to the embodiment of the present invention, the average carbon concentration is almost or completely the same as the carbon concentration of the base material on the inner side (the center of the steel plate in the depth direction) of the second depth region of 10 to 60 μm from the base material surface. Therefore, by setting the C content of the high-strength steel plate to 0.20 to 0.40 mass%, it is possible to ensure that a harder layer exists in a region 60 μm or deeper from the base material surface compared to the second depth region of 10 to 60 μm from the base material surface. The C content of the high-strength steel plate may be 0.21 mass% or more, 0.22 mass% or more, 0.23 mass% or more, or 0.24 mass% or more. Similarly, the C content of the high-strength steel plate may be 0.38 mass% or less, 0.36 mass% or less, or 0.34 mass% or less.

[0034] Plate Thickness The thickness of the high-strength steel plate is not particularly limited, but is preferably 0.2 mm or more from the viewpoint of increasing rigidity, and may be 0.3 mm or more, 0.6 mm or more, 1.0 mm or more, or 2.0 mm or more. On the other hand, if the plate thickness is too thick, the forming load during stretch forming increases, which may lead to wear of the mold and reduced productivity. For this reason, the plate thickness of the high-strength steel plate is preferably 6.0 mm or less, and may be 5.0 mm or less, or 4.0 mm or less.

[0035] More specific embodiments when the above-mentioned preferred high-strength steel sheet is used include embodiment 1 in which the base material surface of the high-strength steel sheet in contact with the zinc-based plating is located on the overlapping interface of multiple overlapping steel sheets, embodiment 2 in which the base material surface is located on the outermost surface (i.e., the electrode side) of multiple overlapping steel sheets, and both (embodiment 3), as described below. [Embodiment 1] The surface of the high-strength steel sheet where the base material is in contact with the zinc-based plating is located at the overlapping surface of the overlapping steel sheets, and precipitates having a diameter of less than 0.1 μm are present at 10 to 200 pieces / μm in a first depth region of 1 to 10 μm from the base material surface. 2 and the amount of solute C in a second depth region of 10 to 60 μm from the surface of the base material is less than 0.20 mass %. [Embodiment 2] The surface of the high-strength steel sheet where the base material is in contact with the zinc-based plating is located on the outermost surface of the multiple overlapping steel sheets, and precipitates having a diameter of less than 0.1 μm are present at 10 to 200 pieces / μm in a first depth region of 1 to 10 μm from the base material surface. 2 and the amount of solute C in a second depth region of 10 to 60 μm from the surface of the base material is less than 0.20 mass %. [Embodiment 3] The surface of the base material of the high-strength steel sheet where the base material is in contact with the zinc-based plating is located on the overlapping surface and the outermost surface of the overlapping multiple steel sheets, and precipitates having a diameter of less than 0.1 μm are present at 10 to 200 pieces / μm in a first depth region 1 to 10 μm from the base material surface. 2 and the amount of solute C in a second depth region of 10 to 60 μm from the surface of the base material is less than 0.20 mass %.

[0036] [The amount of η phase in the zinc-based coating within the corona bond of overlapping surfaces of multiple steel sheets is 20% or less by area] According to a further preferred embodiment of the present invention related to the first and third embodiments, the amount of η phase of the zinc-based plating in the corona bond of the overlapping surfaces of the multiple steel sheets where the base metal surface of the high-strength steel sheet is in contact with the zinc-based plating is 20% by area or less. The η phase of the zinc-based plating means a phase mainly composed of Zn (e.g., Zn content is 95 to 100% by mass) and containing other elements such as Fe in a solid solution state. When alloying between the zinc-based plating and the steel sheet progresses due to the heat input of welding, the ratio of the η phase mainly composed of Zn decreases from the initial zinc-based plating in the corona bond formed on the overlapping surfaces of the steel sheets. By implementing a welding method with a higher heat input compared to a normal welding method, it is possible to further promote alloying between the zinc-based plating and the steel sheet, and therefore it is possible to reduce the amount of η phase of the zinc-based plating in the corona bond to 20% by area or less. The alloying of the zinc-based plating on the overlapping surface side progresses due to the heat input during spot welding, and the melting point of the zinc-based plating increases. Therefore, compared to when the ratio of the η phase is relatively high, it is possible to suppress or reduce the penetration of molten zinc into the steel sheet, and it is possible to further enhance the effect of suppressing LME cracking at the overlapping surface. From the viewpoint of enhancing the effect of suppressing LME cracking, it is preferable that the amount of η phase in the zinc-based coating in the corona bond is smaller, and may be, for example, 18 area % or less or 15 area % or less.

[0037] The area ratio of the η phase in the zinc-based coating in the corona bond is measured as follows. The Zn and Fe element distribution image of the corona bond in the cross section of the weld is taken by SEM-EDS. The η phase in the image is defined as the area where the Zn concentration is 95% or more and the Fe concentration is 5% or less. The part that meets this definition and the other part are binarized by image analysis software, and the area ratio of the η phase in the zinc-based coating in the corona bond is calculated. The measurement area may be, for example, a rectangle of 100 μm in the horizontal direction and 10 μm in the vertical direction. However, the height must be increased according to the thickness of the coating layer in the corona bond. If the total coating layer thickness exceeds 10 μm, the height of the measurement area is set to a value exceeding 10 μm. The area ratio of the η phase is calculated by dividing the area of ​​the η phase in this measurement area by the area of ​​the area where Zn exists in the same area. The area ratio of the η phase is measured at the outer end of the corona bond.

[0038] [The amount of η phase in the zinc-based coating at the weld shoulder of the outermost surfaces of multiple steel sheets is 20% or less by area] According to a further preferred embodiment of the present invention related to the second and third embodiments, the amount of η phase of the zinc-based plating in the weld shoulder of the outermost, i.e., electrode side, surface of the steel sheets where the base metal surface of the high-strength steel sheet is in contact with the zinc-based plating is 20% by area or less. When alloying between the zinc-based plating and the steel sheet progresses due to the heat input of welding, the ratio of η phase mainly composed of Zn decreases from the initial zinc-based plating not only in the corona bond described above but also in the heat affected zone on the electrode side. Therefore, by implementing a welding method with a higher heat input compared to a normal welding method, it is possible to further promote alloying between the zinc-based plating and the steel sheet, and therefore it is possible to reduce the amount of η phase of the zinc-based plating in the heat affected zone on the electrode side to 20% by area or less. In this embodiment, the amount of η phase of the zinc-based plating in the weld shoulder is specified as a representative of the heat affected zone on the electrode side. As explained above, the melting point of the zinc-based plating increases as the alloying of the zinc-based plating on the electrode side progresses due to the heat input during spot welding. Therefore, compared to a case where the ratio of the η phase is relatively high, it is possible to suppress or reduce the penetration of molten zinc into the steel sheet, and it is possible to further enhance the effect of suppressing LME cracking on the electrode side surface. From the viewpoint of enhancing the effect of suppressing LME cracking, it is preferable that the amount of the η phase in the zinc-based coating on the shoulder of the weld is smaller, and may be, for example, 18 area % or less or 15 area % or less.

[0039] The area ratio of the η phase in the zinc-based coating at the shoulder of the weld is measured as follows. Using SEM-EDS, an image of the distribution of Zn and Fe elements in a rectangular area of ​​100 μm in the horizontal direction and 10 μm in the vertical direction is taken, centered on the outer boundary of the shoulder of the weld in the cross section of the weld (the part where the shape suddenly changes from a part with a curvature reflecting the electrode shape due to the electrode pressure during welding to a flat part where the electrode does not contact). However, the height direction must be increased according to the plating layer thickness of the shoulder. If the total plating layer thickness exceeds 10 μm, the height of the measurement area is set to a value exceeding 10 μm. The η phase in the image is defined as the area where the Zn concentration is 95% or more and the Fe concentration is 5% or less. The part that meets this definition and the other parts are binarized using image analysis software, and the area ratio of the η phase in the zinc-based coating at the shoulder of the weld is calculated. Specifically, the area ratio of the η phase is obtained by dividing the area of ​​the η phase in this measurement area by the area of ​​the area where Zn exists in the same area.

[0040] [Preferable chemical composition of high strength steel plate] As described above, the high-strength steel plate according to the embodiment of the present invention may be any material having a tensile strength of 980 MPa or more and having a three-layer structure in which the hardness of the second depth region is controlled to be lower than the hardness of the first and third depth regions in the depth region from the base metal surface in contact with the zinc-based plating. Therefore, the chemical composition of the high-strength steel plate is not particularly limited, and may be appropriately determined within a range that satisfies the above requirements. More specifically, the present invention aims to provide a resistance spot welded joint that includes a high-strength steel plate and can suppress the occurrence of LME cracking during spot welding, as described above, and achieves the objective by using a high-strength steel plate having a tensile strength of 980 MPa or more and a depth region consisting of the above three-layer structure. Therefore, it is clear that the chemical composition of the high-strength steel plate itself is not an essential technical feature for achieving the objective of the present invention. Below, a preferred chemical composition of the high-strength steel plate according to the embodiment of the present invention will be described in detail, but these descriptions are intended to merely exemplify preferred chemical compositions of high-strength steel plates for satisfying the above requirements, and are not intended to limit the present invention to high-strength steel plates having such a specific chemical composition. In the following description, the unit of content of each element, "%", means "mass%" unless otherwise specified. Furthermore, in this specification, "to" indicating a numerical range is used to mean that the numerical values ​​before and after it are included as the lower and upper limits, unless otherwise specified.

[0041] [C:0.20~0.40%] C is an element that inexpensively increases tensile strength and is an important element for controlling the strength of steel. In order to fully obtain such an effect, the C content is preferably 0.20% or more. The C content may be 0.21% or more, 0.22% or more, 0.23% or more, or 0.24% or more. On the other hand, excessive C content may lead to a decrease in elongation. For this reason, the C content is preferably 0.40% or less. The C content may be 0.38% or less, 0.36% or less, or 0.34% or less.

[0042] [Si: 0.01-2.00%] Si acts as a deoxidizer and is an element that suppresses the precipitation of carbides during the cooling process during cold-rolled sheet annealing. In order to fully obtain such an effect, the Si content is preferably 0.01% or more. The Si content may be 0.10% or more, 0.30% or more, or 0.80% or more. On the other hand, excessive Si content may increase the steel strength and decrease the elongation. For this reason, the Si content is preferably 2.00% or less. The Si content may be 1.80% or less, 1.50% or less, or 1.20% or less.

[0043] [Mn: 0.10~4.00%] Mn is a factor that affects the ferrite transformation of steel, and is an element that is effective in increasing strength. In order to fully obtain such effects, the Mn content is preferably 0.10% or more. The Mn content may be 0.50% or more, 1.00% or more, or 1.50% or more. On the other hand, excessive Mn content may increase the steel strength but decrease the elongation. For this reason, the Mn content is preferably 4.00% or less. The Mn content may be 3.30% or less, 3.00% or less, or 2.70% or less.

[0044] [P:0.0200% or less] P is an element that strongly segregates at ferrite grain boundaries and promotes grain boundary embrittlement. The lower the P content, the better, and ideally it is 0%. However, since excessive reduction in the P content leads to a significant increase in costs, the P content may be 0.0001% or more, or 0.0010% or more, or 0.0050% or more. On the other hand, excessive P content may lead to embrittlement of the steel due to grain boundary segregation as described above. For this reason, the P content is preferably 0.0200% or less. The P content may be 0.0180% or less, 0.0150% or less, or 0.0100% or less.

[0045] [S:0.0200% or less] S is an element that generates nonmetallic inclusions such as MnS in steel, which leads to a decrease in the ductility of steel parts. The lower the S content, the better, so ideally it is 0%. However, since excessive reduction in the S content leads to a significant increase in costs, the S content may be 0.0001% or more, or may be 0.0002% or more, 0.0010% or more, or 0.0050% or more. On the other hand, excessive S content may lead to the occurrence of cracks originating from nonmetallic inclusions during cold forming. For this reason, the S content is preferably 0.0200% or less. The S content may be 0.0180% or less, 0.0150% or less, or 0.0100% or less.

[0046] [Al: 1.500% or less] Al is an element that acts as a deoxidizer for steel and stabilizes ferrite, and may be contained as necessary. Since Al may not be contained, the lower limit of the Al content is 0%. In order to fully obtain the effect, the Al content is preferably 0.001% or more, and may be 0.010% or more, 0.050% or more, or 0.100% or more. On the other hand, if Al is contained excessively, the strength of the steel sheet may decrease because the ferrite transformation and bainite transformation during the cooling process in the annealing of the cold-rolled sheet are excessively promoted. For this reason, the Al content is preferably 1.500% or less. The Al content may be 1.400% or less, 1.200% or less, or 1.000% or less.

[0047] [N:0.0200% or less] N is an element that forms coarse nitrides in the steel sheet and reduces the workability of the steel sheet. In addition, N is an element that causes blowholes during welding. The lower the N content, the better, so ideally it is 0%. However, excessive reduction in the N content leads to a significant increase in manufacturing costs, so the N content may be 0.0001% or more, or may be 0.0005% or more, 0.0010% or more, or 0.0050% or more. On the other hand, if N is contained excessively, it combines with Ti to generate a large amount of TiN, so the amount of solid solution Ti in the steel sheet decreases, and the generation of precipitates (e.g., Ti oxides) on the surface layer of the steel sheet may become uncontrollable. For this reason, the N content is preferably 0.0200% or less. The N content may be 0.0150% or less, 0.0100% or less, or 0.0080% or less.

[0048] [Ti: 0.005~0.500%] Ti is an element necessary for forming fine precipitates (e.g., Ti oxides) on the surface layer of the steel sheet by combining with oxygen penetrating from the annealing atmosphere into the surface layer of the steel during the heating and soaking processes in the cold-rolled sheet annealing. In order to sufficiently form such precipitates, the Ti content is preferably 0.005% or more. The Ti content may be 0.010% or more, 0.050% or more, 0.100% or more, or 0.150% or more. On the other hand, excessive Ti content may cause the formation of excessive precipitates or promote ferrite transformation in the cooling process during cold-rolled sheet annealing, causing a decrease in strength. For this reason, the Ti content is preferably 0.500% or less. The Ti content may be 0.450% or less, 0.400% or less, 0.350% or less, or 0.300% or less.

[0049] The preferred basic chemical composition of the high-strength steel sheet is as described above. Furthermore, the high-strength steel sheet may contain, as necessary, Co: 0-0.5000%, Ni: 0-1.0000%, Mo: 0-1.0000%, Cr: 0-2.0000%, O: 0-0.0200%, B: 0-0.0100%, Nb: 0-0.5000%, V: 0-0.5000%, Cu: 0-0.5000%, W: 0-0.1000%, T: 0-0.200%, and / or Fe: 0-0.200%. The composition may contain one or more elements selected from the group consisting of a: 0-0.1000%, Sn: 0-0.0500%, Sb: 0-0.0500%, As: 0-0.0500%, Mg: 0-0.0500%, Ca: 0-0.0500%, Y: 0-0.0500%, Zr: 0-0.0500%, La: 0-0.0500%, and Ce: 0-0.0500%. The content of each element may be 0.0001% or more, 0.0005% or more, or 0.0010% or more.

[0050] In the high-strength steel plate according to the embodiment of the present invention, the balance other than the above elements consists of Fe and impurities. The impurities are components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, when industrially manufacturing the high-strength steel plate.

[0051] The chemical composition of the high-strength steel sheet may be measured by a general analytical method. For example, the chemical composition of the high-strength steel sheet may be measured by inductively coupled plasma-atomic emission spectrometry (ICP-AES). C and S may be measured by the combustion-infrared absorption method, N by the inert gas fusion-thermal conductivity method, and O by the inert gas fusion-non-dispersive infrared absorption method. When the high-strength steel sheet has a zinc-based plating on its surface, the zinc-based plating may be removed by mechanical grinding before the chemical composition is analyzed.

[0052] [Manufacturing method for high-strength steel plates] Next, a preferred method for manufacturing a high-strength steel plate according to an embodiment of the present invention will be described. The following description is intended to exemplify a characteristic method for manufacturing a high-strength steel plate according to an embodiment of the present invention, but is not intended to limit the high-strength steel plate to one manufactured by the manufacturing method described below.

[0053] A method for producing a high strength steel plate according to an embodiment of the present invention may, for example, include the steps of hot rolling a steel billet having the chemical composition described above in relation to the high strength steel plate, and then coiling the billet at 580°C or less; A step of pickling the obtained hot-rolled steel sheet to remove oxide scale present on the surface of the hot-rolled steel sheet and to remove at least 5 μm of the surface layer of the hot-rolled steel sheet; A process of cold rolling the hot-rolled steel sheet and then annealing the same, the annealing process comprising holding the obtained cold-rolled steel sheet in a temperature range of 200 to 400°C in an atmosphere having a dew point of -20 to 20°C for 20 to 180 seconds, and then holding the cold-rolled steel sheet in a temperature range of 740 to 900°C in an atmosphere having a dew point of -20 to 20°C for 45 to 300 seconds. Each step will be described in detail below.

[0054] [Hot rolling and coiling process] In this process, a steel billet having the chemical composition described above in relation to the high strength steel plate is subjected to hot rolling. The steel billet used is preferably cast by a continuous casting method from the viewpoint of productivity, but may be produced by an ingot casting method or a thin slab casting method. In addition, the cast steel billet may be subjected to rough rolling before finish rolling as an option, in order to adjust the plate thickness, etc. Such rough rolling may be performed under no particular conditions, as long as the desired sheet bar dimensions are secured. Hot rolling is generally performed under conditions such that the finishing rolling completion temperature is 650°C or higher, although there are no particular limitations. If the finishing rolling completion temperature is too low, the rolling reaction force increases, making it difficult to stably obtain the desired plate thickness. Although there are no particular limitations on the upper limit, the finishing rolling completion temperature is generally 950°C or lower.

[0055] [Winding temperature] After hot rolling, the obtained hot-rolled steel sheet is coiled at a coiling temperature of 580°C or less. The coiling temperature is an important factor for controlling the transformation behavior of the steel structure from austenite to ferrite, pearlite, bainite, and martensite, as well as controlling the precipitation behavior of Ti. If the steel sheet is coiled at a relatively high temperature, coarse Ti precipitates may be generated in the steel structure after coiling. In such a case, it becomes impossible to impart a sufficient gradient of properties (strength, hardness, etc.) to the surface layer structure of the steel sheet after cold-rolled sheet annealing, which will be described in detail later (i.e., a gradient of properties such that the hardness of the second depth region is lower than the hardness of the first depth region). Therefore, in order to suppress the generation of such coarse Ti precipitates, it is preferable that the coiling temperature is as low as possible, specifically, 580°C or less. The coiling temperature is preferably 550°C or less. For example, the coiling temperature may be room temperature or less, but in order to coil the steel sheet at a temperature below room temperature, it is necessary to lower the temperature of the water for cooling the steel sheet to room temperature or less, which causes an increase in manufacturing costs. Furthermore, since the residual stress in the steel sheet increases due to rapid cooling, for example, if the steel sheet is coiled at a temperature below 10° C., the steel sheet may crack when uncoiling in the subsequent pickling process, resulting in reduced productivity. Therefore, although not particularly limited, the lower limit of the coiling temperature is generally 10° C. or higher, and preferably 50° C. or higher.

[0056] [Pickling process] The coiled hot-rolled steel sheet is rewound and subjected to pickling. By pickling, the oxide scale present on the surface of the hot-rolled steel sheet can be removed, and the chemical conversion property and plating property of the cold-rolled steel sheet can be improved. The oxide scale refers to an oxide layer (external oxide layer) formed on the surface of the steel sheet, and includes fayalite (Fe2SiO4), a composite oxide of FeO and SiO2 formed at the interface with the steel sheet. In addition, pickling promotes dissolution of the surface layer of the steel sheet, and the oxide (internal oxide) formed under the oxide scale in the surface layer of the hot-rolled steel sheet, i.e., inside the steel sheet, is also completely removed. By completely removing the oxide formed inside the steel sheet, that is, by making the thickness of the internal oxide layer formed inside the steel sheet 0 μm, it is possible to suppress the bonding of Ti in the steel with oxygen and to allow Ti to exist in a solid solution state. Here, the thickness of the internal oxide layer refers to the distance from the surface of the steel sheet to the furthest position where the internal oxide exists when proceeding from the surface of the steel sheet in the thickness direction of the steel sheet (direction perpendicular to the surface of the steel sheet). By leaving the solid solution Ti from the new surface that appears after pickling to the inside of the sheet thickness, many fine Ti precipitates can be formed in the outermost layer of the steel sheet after annealing the cold-rolled sheet, and as a result, a sufficient gradient in properties can be imparted to the surface layer structure. Pickling may be performed once, but in order to more reliably remove the oxides in the steel that have formed under the oxide scale of the hot-rolled steel sheet, it may be performed multiple times, and mechanical polishing with a grinding brush or the like may be performed before and after pickling. In addition, instead of measuring the change in sheet thickness before and after pickling, the amount of removal of the steel sheet surface layer may be determined from the change in coil weight before and after pickling. If the amount of removal of the steel sheet surface layer is less than 5 μm, the oxides under the oxide scale are not completely removed, that is, the thickness of the internal oxide layer exceeds 0 μm, and in the heating process during annealing of the cold-rolled sheet, oxygen is supplied from the internal oxides remaining in the steel sheet surface layer, causing Ti oxides to precipitate and coarsen in the steel sheet surface layer, and it becomes impossible to impart a sufficient gradient in properties to the surface layer structure of the steel sheet after annealing of the cold-rolled sheet. For this reason, the amount of the steel sheet surface layer removed is 5 μm or more, more specifically 5 μm or more on one side, preferably 7 μm or more, and more preferably 10 μm or more. Although the greater the amount of the steel sheet surface layer removed by pickling, the better, excessive steel corrosion causes a decrease in the pickling speed and a decrease in yield, resulting in a decrease in productivity.Therefore, the upper limit is generally 150 μm or less, and may be 120 μm or less, 100 μm or less, 70 μm or less, 50 μm or less, or 30 μm or less.

[0057] [Cold rolling and annealing process] Finally, the obtained hot-rolled steel sheet is subjected to cold rolling and then a predetermined annealing (hereinafter also referred to as "cold-rolled sheet annealing") to obtain a high-strength steel sheet according to an embodiment of the present invention. The reduction in cold rolling is not particularly limited and may be any appropriate value. For example, the reduction may be 5% or more, 10% or more, or 30% or more, and / or 90% or less, 75% or less, or 50% or less. Hereinafter, cold-rolled sheet annealing will be described in detail.

[0058] [Cold-rolled sheet annealing] [Dew point in the temperature range of 200~400℃] In the heating process during annealing of cold-rolled sheets, increasing the dew point of the gas atmosphere in the furnace, specifically controlling the dew point within the range of -20 to 20°C, promotes the penetration of oxygen into the steel sheet, and produces fine Ti precipitates in the outermost surface layer of the steel sheet. These fine Ti precipitates act as nuclei, and in the soaking treatment following the heat treatment, precipitates less than 0.1 μm in diameter are produced at a density of 10 precipitates / μm in the first depth region of 1 to 10 μm from the surface of the base material. 2 or more, and the hardness of the outermost layer of the steel sheet after cold-rolled sheet annealing can be increased. If the dew point is too low, the amount of oxygen penetrating into the steel sheet is insufficient, and the number of nuclei of fine Ti precipitates is reduced, so that a sufficient amount of precipitates cannot be precipitated in the outermost layer of the steel sheet after cold-rolled sheet annealing. Therefore, the lower limit of the dew point is -20°C or more, preferably -15°C or more. On the other hand, if the dew point is high, the amount of oxygen penetrating into the steel sheet becomes excessive, and coarse Ti precipitates are generated at a low number density. Therefore, the upper limit of the dew point is 20°C or less, preferably 15°C or less.

[0059] [Holding time in the temperature range of 200-400℃] In the heating process during cold-rolled sheet annealing, in order to produce fine Ti precipitates in the outermost layer of the steel sheet, it is effective to control the holding time in the temperature range of 200 to 400 ° C. together with the dew point. Here, the holding time refers to the time spent in the temperature range of 200 to 400 ° C., and therefore includes the time when the temperature is gradually raised between 200 and 400 ° C. If the holding time is short, the amount of oxygen penetrating into the steel sheet is insufficient, and the number of nuclei of fine Ti precipitates is reduced, so that it is not possible to precipitate a sufficient amount of precipitates in the outermost layer of the steel sheet after cold-rolled sheet annealing. For this reason, the lower limit of the holding time is 20 seconds or more, preferably 30 seconds or more. On the other hand, if the holding time is long, the amount of oxygen penetrating into the steel sheet becomes excessive, and coarse Ti precipitates are generated at a low number density. For this reason, the upper limit of the holding time is 180 seconds or less, preferably 150 seconds or less.

[0060] [Dew point in the temperature range of 740-900℃] In cold-rolled sheet annealing, the dew point and holding time in the temperature range of 200 to 400 ° C are optimized to generate fine Ti precipitates in the outermost layer of the steel sheet, and then the dew point at 740 to 900 ° C is controlled using these fine Ti precipitates as nuclei, so that a sufficient amount of precipitates can be precipitated in the outermost layer of the steel sheet. Furthermore, holding at 740 to 900 ° C promotes the diffusion of alloy elements in the steel compared to holding at 200 to 400 ° C, so that C dissolved in the steel combines with oxygen and is desorbed into the atmosphere (decarburization reaction), resulting in a decrease in the amount of dissolved C. This effect reduces the amount of dissolved C in the second depth region of 10 to 60 μm from the base metal surface to less than 0.20 mass%, making it possible to newly create a soft layer in this region. If the dew point is too low, the amount of oxygen penetrating into the steel sheet is insufficient, so that the Ti precipitates and the Si and Mn oxides with the Ti precipitates as nuclei are not sufficiently coarsened, and the precipitates cannot be precipitated in sufficient amounts in the outermost layer of the steel sheet after cold-rolled sheet annealing, and the amount of solute C in the second depth region of 10 to 60 μm from the base material surface cannot be reduced. Therefore, the lower limit of the dew point is -20°C or higher, preferably -15°C or higher. On the other hand, if the dew point is high, the amount of oxygen penetrating into the steel sheet becomes excessive, and the coarsening and coalescence of the Ti precipitates and the Si and Mn oxides with the Ti precipitates as nuclei cannot be suppressed, and the number density of the precipitates decreases. Therefore, the upper limit of the dew point is 20°C or lower, preferably 15°C or lower.

[0061] [Holding time in the temperature range of 740-900℃] In cold-rolled sheet annealing, the dew point and holding time in the temperature range of 200 to 400 ° C are optimized to generate fine Ti precipitates in the outermost layer of the steel sheet, and then the holding time at 740 to 900 ° C is controlled using these fine Ti precipitates as nuclei, so that a sufficient amount of precipitates can be precipitated in the outermost layer of the steel sheet. Furthermore, holding at 740 to 900 ° C promotes the diffusion of alloy elements in the steel compared to holding at 200 to 400 ° C, so that C dissolved in the steel combines with oxygen and is desorbed into the atmosphere (decarburization reaction), resulting in a decrease in the amount of dissolved C. Due to this effect, the amount of dissolved C in the second depth region of 10 to 60 μm from the surface of the base material can be reduced to less than 0.20 mass%, making it possible to newly create a soft layer in this region. Here, the holding time refers to the time spent in the temperature range of 740 to 900 ° C, and therefore includes the time when the temperature is gradually increased between 740 and 900 ° C. If the holding time is short, the amount of oxygen penetrating into the steel sheet is insufficient, so that the coarsening of Ti precipitates and Si and Mn oxides with the Ti precipitates as nuclei is insufficient, and a sufficient amount of precipitates cannot be precipitated in the outermost layer of the steel sheet after cold-rolled sheet annealing, and in addition, the amount of dissolved C in the second depth region of 10 to 60 μm from the base material surface cannot be reduced. Therefore, the lower limit of the holding time is 45 seconds or more, preferably 48 seconds or more or 60 seconds or more. On the other hand, if the holding time is long, the amount of oxygen penetrating into the steel sheet becomes excessive, and the coarsening and coalescence of Ti precipitates and Si and Mn oxides with the Ti precipitates as nuclei cannot be suppressed, and the number density of precipitates decreases. Therefore, the upper limit of the holding time is 300 seconds or less, preferably 250 seconds or less.

[0062] In the manufacturing method of a high-strength steel sheet according to an embodiment of the present invention, as described above, Ti is contained in order to form fine precipitates (e.g., Ti oxides) in the surface layer of the steel sheet. More specifically, by coiling the Ti-containing hot-rolled steel sheet at a relatively low coiling temperature of 580°C or less in the coiling process, the generation of coarse Ti precipitates in the steel structure is suppressed, and by removing an amount of 5 μm or more from the surface layer of the hot-rolled steel sheet in the subsequent pickling process, internal oxides are also completely removed in addition to external oxides, and Ti in the steel is suppressed from combining with oxygen, making it possible for Ti to exist in a solid solution state. Next, in the annealing step, fine Ti precipitates are generated by controlled annealing at 200 to 400°C (dew point: -20 to 20°C, holding time: 20 to 180 seconds), and then, by controlled annealing at 740 to 900°C (dew point: -20 to 20°C, holding time: 40 to 300 seconds), precipitates can be precipitated in a sufficient amount in the outermost layer of the steel sheet using the fine Ti precipitates as nuclei. The hardness of the outermost layer can be increased by precipitation strengthening caused by such precipitates. Furthermore, the diffusion of alloy elements in the steel is promoted at such high temperatures, and C dissolved in the steel is combined with oxygen and desorbed into the atmosphere, so that the amount of dissolved C in the second depth region of 10 to 60 μm from the surface of the base material can be reduced to less than 0.20 mass%. As a result, a layer softer than the outermost layer can be formed in this region. That is, in the manufacturing method of a high-strength steel sheet according to an embodiment of the present invention, the presence of Ti is assumed, and by appropriately controlling the manufacturing conditions of the steel containing Ti, particularly in the coiling process, pickling process, and annealing process, it is possible to impart a sufficient gradient in properties such as hardness to the surface structure of the steel sheet.

[0063] The operations such as cooling, tempering and plating treatment after annealing are not particularly limited, and may be carried out under any appropriate conditions appropriately selected in consideration of other desired properties.

[0064] [Steel plates other than high-strength steel plates] Any suitable steel plate can be used as the steel plate other than the high-strength steel plate described above among the multiple steel plates used in the resistance spot welded joint according to the embodiment of the present invention. Such a steel plate may be, for example, a high-strength steel plate having a tensile strength of 980 MPa or more and not having the above-mentioned three-layer structure in the depth region from the base metal surface. On the other hand, when such a steel plate is a low-strength steel plate, the chemical composition, metal structure, shape, etc. of the steel plate are not particularly limited except that the tensile strength is less than 980 MPa. Therefore, for steel plates other than the high-strength steel plate described above, an appropriate steel plate may be appropriately selected according to the application and desired characteristics of the resistance spot welded joint, for example, the desired joint strength.

[0065] [Zinc-based plating] The zinc-based plating is not particularly limited and may be any appropriate zinc-based plating. The zinc-based plating may be either hot-dip galvanizing or electrogalvanizing. Hot-dip galvanizing includes, for example, hot-dip galvanizing (GI) as well as alloyed hot-dip galvanizing (GA), hot-dip Zn-Al alloy plating, hot-dip Zn-Al-Mg alloy plating, hot-dip Zn-Al-Mg-Si alloy plating, etc. Electrical galvanizing includes, for example, electric Zn-Ni alloy plating as well as electric galvanizing (EG). Preferably, the zinc-based plating is hot-dip galvanizing (GI), alloyed hot-dip galvanizing (GA), or electric galvanizing (EG). The coating weight is not particularly limited and may be a general coating weight. The zinc-based plating may be in contact with the base material of the high-strength steel plate in the final resistance spot welded joint, and may be applied to either the high-strength steel plate or the other steel plate before spot welding.

[0066] <Method of manufacturing resistance spot welded joints> The resistance spot welded joint according to the embodiment of the present invention can be manufactured by using any suitable spot welding method known to those skilled in the art to manufacture a plurality of steel sheets obtained by applying zinc-based plating to the high-strength steel sheet and overlapping it with another steel sheet, or a plurality of steel sheets obtained by overlapping the high-strength steel sheet with another steel sheet having zinc-based plating. Therefore, for example, the resistance spot welded joint according to the embodiment of the present invention can be manufactured by forming a corona bond around a nugget and the nugget by applying pressure to the plurality of overlapping steel sheets as described above using a pair of opposing electrodes and passing current between the electrodes under normal conditions. Below, a more preferable manufacturing method of a resistance spot welded joint that can further suppress LME cracking compared to such a normal spot welding method will be described in detail.

[0067] [Manufacturing method 1: Using a downslope] The manufacturing method 1 includes a step of pressing a plurality of overlapping steel sheets, including a high-strength steel sheet having a zinc-based plating or including a steel sheet having a zinc-based plating and a high-strength steel sheet adjacent to the above-mentioned steel sheet, using a pair of opposing electrodes (S1); a step (S2) of forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; a step of continuously reducing the current value between the electrodes to 0 while maintaining pressure on the steel plates (S3); The present invention is characterized by the following.

[0068] FIG. 4 is a diagram showing a schematic diagram of a change in current over time in the manufacturing method 1. Referring to FIG. 4, in step S1, a plurality of steel sheets including a high-strength steel sheet are pressed using a pair of opposing electrodes, and then in step S2, a current is passed between the electrodes while pressing the plurality of steel sheets to form a nugget and a corona bond. Then, in step S3, the current value between the electrodes is continuously reduced to 0 while maintaining pressure on the plurality of steel sheets. By utilizing such a continuous reduction in the current value, that is, the downslope of the current value, it is possible to suppress the increase in tensile stress during cooling, compared to the case where the current value I is rapidly reduced in one step. LME cracking occurs due to the action of tensile stress generated during welding. Therefore, by suppressing the increase in tensile stress by the manufacturing method using such a downslope of the current value, it is possible to suppress the occurrence of LME cracking. In addition, by utilizing the downslope of the current value, it is possible to increase the welding heat input, compared to the case where the current value is rapidly reduced in one step, and therefore it is possible to promote alloying between the zinc-based coating and the steel sheet. As a result, it is possible to reduce the amount of η-phase in the zinc-based coating in the corona bond and / or the shoulder of the weld, more specifically to 20% by area or less. Since the melting point of the zinc-based coating is increased by such alloying, it is possible to suppress or reduce the penetration of molten zinc into the steel sheet compared to the case where the ratio of η-phase is relatively high, and it is possible to further enhance the effect of suppressing LME cracking on the overlap surface and / or the electrode side surface of the steel sheet.

[0069] [Preferred embodiment of production method 1] A preferred embodiment of the manufacturing method 1 includes a step of pressing a plurality of overlapping steel sheets, including a high-strength steel sheet having a zinc-based plating or including a steel sheet having a zinc-based plating and a high-strength steel sheet adjacent to the above-mentioned steel sheet, using a pair of opposing electrodes (S1); a step (S2) of forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; a step of continuously reducing the current value between the electrodes to 0 while maintaining pressure on the steel plates (S3); a current value I between the electrodes at a time when the formation of the nugget is completed and an average value Iave of a current value between the electrodes during a first period that is a period from the time when the formation of the nugget is completed to a time when the current value is set to 0 satisfy a relationship of 0.30×I≦Iave≦0.90×I, The length of a second period, which is a period from the time when the current value is set to 0.90×I to the time when the current value is set to 0.30×I, is set to 420 msec or more, and The pressurizing force during the first period is always set to 1.1 times or more the pressurizing force P at the time when the formation of the nugget is completed.

[0070] FIG. 5 is a diagram showing the change over time of the electric current and the pressing force in a preferred embodiment of the manufacturing method 1. Referring to FIG. 5, first, in step S1, a plurality of steel sheets including a high-strength steel sheet are pressed by a pair of opposing electrodes, and then in step S2, a current is passed between the electrodes while pressing the plurality of steel sheets, thereby forming a nugget and a corona bond. Next, in step S3, during the first period corresponding to the period of step S3, that is, the first period corresponding to the period from the time when the formation of the nugget is completed to the time when the current value is set to 0, the pressing force is always maintained at 1.1 times the pressing force P at the time when the formation of the nugget is completed, while the current value I between the electrodes is continuously reduced to 0. In addition, in this embodiment, during the first period, the average value Iave corresponding to the average of the time integral value of the current value between the electrodes satisfies the relationship of 0.30×I≦Iave≦0.90×I, and further, the length of the second period corresponding to the period from the time when the current value is set to 0.90×I to the time when the current value is set to 0.30×I is controlled to be 420 msec or more. LME cracking occurs when a tensile stress is applied to a high-strength steel sheet in contact with liquid zinc, and such tensile stress is likely to increase when the electrode is released. For example, in a corona bond, the high-strength steel sheet can come into contact with liquid zinc when the temperature of the corona bond is below 907°C (the temperature at which zinc vapor may liquefy) and above 420°C (the temperature at which liquid zinc may solidify). Therefore, by maintaining the pressure applied by the electrode for a period until the temperature of the corona bond is reliably below about 420°C, preferably for a first period, at 1.1 times or more the pressure P at the time when the formation of the nugget is completed, the tensile stress generated in the corona bond while the high-strength steel sheet is in contact with the liquid zinc can be mitigated.

[0071] In addition, if the current value I at the time when the formation of the nugget is completed and the average current value Iave in the first period satisfy the relationship of 0.30×I≦Iave≦0.90×I, and the length of the second period is set to 420 msec or more, the cooling rate of the welded portion decreases. In this case, the heat removal by the electrode is reduced, and the heat transfer from the welded portion to the surrounding steel plate is promoted. As a result, when the temperature of the welded portion decreases, the contraction of the welded portion becomes gentle, while the restraining force of the welded portion by the steel plate around the welded portion becomes smaller. It is considered that the tensile stress in the welded portion is further reduced by such a mechanism. Therefore, according to a preferred embodiment of the manufacturing method 1, it is possible to achieve a higher LME crack suppression effect than the LME crack suppression effect by using the downslope described in relation to the manufacturing method 1. Although not particularly limited, I and Iave may be controlled to satisfy the relationship of 0.45×I≦Iave≦0.85×I.

[0072] [Manufacturing method 2: Use of post-energization] The manufacturing method 2 includes a step of pressing a plurality of overlapping steel sheets, including a high-strength steel sheet having a zinc-based plating or including a steel sheet having a zinc-based plating and a high-strength steel sheet adjacent to the above-mentioned steel sheet, using a pair of opposing electrodes (S1); a step (S2) of forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; A step of reducing the current value between the electrodes to 0 while maintaining pressure on the steel plates (S3). The current value between the electrodes at the time when the formation of the nugget is completed is defined as I, and 1 / 2 of the total sheet thickness of the steel sheet in mm is defined as tm. The method is characterized in that, when the current value between the electrodes is reduced to 0 or within less than 0.04 seconds after it is reduced to 0, the current value between the electrodes is maintained at a constant value of 0.12×tm or more per sec within a range of 0.9×I to 0.3×I.

[0073] FIG. 6 is a diagram showing a schematic diagram of a change in current with time in manufacturing method 2. Referring to FIG. 6, in step S1, a plurality of steel sheets including a high-strength steel sheet are pressed using a pair of opposing electrodes, and then in step S2, current is applied between the electrodes while applying pressure to the plurality of steel sheets to form a nugget and a corona bond. Then, in step S3, when the current value between the electrodes is reduced to 0 while maintaining pressure on the plurality of steel sheets, the current value I in step S2 is held at a constant value within a range of 0.9×I to 0.3×I for a predetermined time. In the process in which the weld metal solidifies during spot welding, elements such as P contained in the weld metal may solidify and reduce the strength of the joint. In response to this, after forming a nugget and a corona bond in step S2, the current value I is not suddenly lowered, but is held at a constant value within a range of 0.9×I to 0.3×I for a predetermined time (post-current application), so that the solidification segregation can be dispersed, and such a segregation mitigation effect can suppress a decrease in the strength of the joint. In addition, by using such post-current, as in the case of using the downslope, the welding heat input can be increased compared to the case where the current value I is rapidly reduced in one step, and therefore the alloying between the zinc-based coating and the steel sheet can be promoted. As a result, the amount of η-phase in the zinc-based coating in the corona bond and / or the shoulder of the weld can be reduced, more specifically, to 20% by area or less. Since the melting point of the zinc-based coating is increased by such alloying, the penetration of molten zinc into the steel sheet can be suppressed or reduced compared to the case where the ratio of η-phase is relatively high, and the effect of suppressing LME cracking on the overlap surface and / or the electrode side surface of the steel sheet can be further enhanced.

[0074] From the viewpoint of reliably obtaining the above-mentioned segregation mitigation effect and alloying promotion effect, the current value during post-current application is preferably high, specifically, a constant value within the range of 0.9×I to 0.8×I. The holding time needs to be longer as the total thickness of the overlapped steel sheets becomes thicker. Specifically, the holding time needs to be 0.12×tm or more in units of sec, where tm is defined as 1 / 2 of the total thickness of the steel sheets in units of mm. The upper limit is not particularly limited, but for example, the holding time may be 0.6 sec or less. From the viewpoint of enhancing the segregation mitigation effect, it is preferable to hold the current value at a constant value within the range of 0.9×I to 0.3×I without passing through a cooling time without current application in step S3. However, if it is a relatively short time, the current value may be held at the above-mentioned constant value after passing through a cooling time without current application in step S3. Such a cooling time (non-current application time) is preferably less than 0.04 seconds or 0.03 seconds or less after the current value is reduced to 0. This makes it possible to maintain the segregation mitigation effect to a certain extent, while further enhancing the effect of suppressing LME cracking on the overlapping surfaces and / or the electrode side surfaces of the steel sheets based on the alloying promotion effect. The current value I is not particularly limited, but is generally 5 to 12 kA.

[0075] [Manufacturing method 3: Pre-energization] The manufacturing method 3 includes a step of pressing a plurality of overlapping steel sheets, including a high-strength steel sheet having a zinc-based plating or including a steel sheet having a zinc-based plating and a high-strength steel sheet adjacent to the above-mentioned steel sheet, using a pair of opposing electrodes; A step of preheating the steel sheets by applying a pre-current between the electrodes while pressing the plurality of steel sheets; forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; The present invention is characterized by the following.

[0076] In the manufacturing method 3, by performing a preliminary current before the main current to form the nugget and the corona bond, the welding heat input can be increased compared to the case where the preliminary current is not performed, and therefore the alloying between the zinc-based coating and the steel sheet can be promoted. As a result, as in the manufacturing methods 1 and 2, it is possible to reduce the amount of η phase of the zinc-based coating in the corona bond and / or the shoulder of the weld to 20 area % or less. As a result, it is possible to suppress or reduce the penetration of molten zinc into the steel sheet, and it is possible to further enhance the effect of suppressing LME cracking on the overlap surface and / or the electrode side surface of the steel sheet. The specific conditions of the preliminary current are not particularly limited, and any appropriate conditions known to those skilled in the art may be selected. For example, the preliminary current may be performed by passing a constant current value lower than the main current for a predetermined time, or may be a current that gradually increases the current, i.e., an upslope current.

[0077] [Manufacturing method 4: Extension of retention] The manufacturing method 4 includes a step of pressing a plurality of overlapping steel sheets, including a high-strength steel sheet having a zinc-based plating or including a steel sheet having a zinc-based plating and a high-strength steel sheet adjacent to the above-mentioned steel sheet, using a pair of opposing electrodes (S1); a step (S2) of forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; A step (S3) of reducing a current value between the electrodes to 0 while maintaining pressure on the steel plates; a step of maintaining the applied pressure at 0.8×P or more for 0.2 sec to 0.4 sec with the current value between the electrodes at 0 (S4); and P is the pressure applied when the formation of the nugget is completed.

[0078] In manufacturing method 4, after the current value between the electrodes is reduced to 0, the electrodes are not immediately released, but are held for a predetermined period of time and pressure for an extended period of time, and then released to reduce the generation of tensile stress. To explain in more detail, first, in step S1, the steel sheet is pressed by the electrodes at room temperature, increasing the tensile stress applied to the steel sheet, and then, with the temperature rise caused by the passage of current in step S2, the material strength of the steel sheet decreases and the tensile stress decreases. Next, when the passage of current is stopped in step S3, the steel sheet is cooled, and the tensile stress is restored accordingly. If the electrodes are released in this state immediately or after a relatively short holding time, the tensile stress increases significantly at the moment of release, and since the molten zinc is in a relatively high temperature state, the risk of LME cracking increases. Therefore, in the manufacturing method 4, after step S3, the pressure is slightly reduced in step S4 and held for 0.2 sec to 0.4 sec, which suppresses the increase in tensile stress compared to when the electrode is released immediately or after a relatively short holding time of about 0.1 sec. Furthermore, since the electrode is released after the temperature is sufficiently lowered, the molten zinc can be completely or sufficiently solidified. Therefore, according to the manufacturing method 4, it is possible to greatly reduce the risk of LME cracking compared to when step S4 is not included. If the electrode holding time is longer than 0.4 sec, the quenching speed of the welded part increases and the hardness of the welded part may tend to increase. In this case, the toughness of the welded part, especially the nugget, may deteriorate, and the joint strength and hydrogen embrittlement resistance may become inferior, so the electrode holding time is set to an upper limit of 0.4 sec. From the viewpoint of enhancing the effect of reducing the tensile stress, the pressure in step S4 needs to be 0.8×P or more with respect to the pressure P in step S2, i.e., the pressure P at the time when the formation of the nugget is completed. The upper limit is not particularly limited, but for example, the pressure in step S4 may be 0.9×P. The pressure P is not particularly limited, but is generally 2 to 8 kN.

[0079] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. EXAMPLES

[0080] In the following examples, high-strength steel plates were manufactured under various conditions, and the obtained high-strength steel plates were used to manufacture resistance spot welded joints according to embodiments of the present invention by a plurality of manufacturing methods, and the occurrence of LME cracking during the manufacture was investigated.

[0081] [Example 1] [Manufacturing of high-strength steel plates] Steel having a chemical composition consisting of, in mass%, C: 0.22% or 0.24%, Si: 0.41%, Mn: 0.64%, P: 0.0190%, S: 0.0038%, Al: 0.717%, N: 0.0021%, Ti: 0.470%, and the balance: Fe and impurities was melted to produce steel billets. These steel billets were inserted into a furnace heated to 1220°C, and subjected to a homogenization treatment in which they were held for 60 minutes, after which they were taken out into the atmosphere and hot-rolled to obtain steel plates having a thickness of 2.6 mm. The finishing rolling temperature in the hot rolling was 910°C, and the billets were cooled to 550°C and coiled. Next, the oxide scale of this hot-rolled steel sheet was removed from the surface layer of both sides of the steel sheet by pickling to a thickness of 10 μm on each side (the thickness of the internal oxide layer after pickling and before cold rolling was 0 μm), and cold rolling was performed at a rolling reduction rate of 45% to finish the sheet thickness to 1.6 mm. Furthermore, this cold-rolled steel sheet was annealed, specifically, when the temperature was raised to 860 ° C, the temperature range of 200 to 400 ° C was controlled to an atmosphere with a dew point of -5 ° C (25 ° C for comparative steel sheets 1 and 2), and the holding time in that temperature range was 30 seconds, and in addition, the temperature range of 740 to 900 ° C was controlled to an atmosphere with a dew point of 5 ° C, and the holding time in that temperature range was 120 seconds (35 seconds for comparative steel sheet 1). Finally, the cold-rolled steel sheet was cooled under specified conditions, and then subjected to galvannealing (GA) under normal conditions to produce high-strength steel sheets having zinc-based plating (high-strength steel sheets 1 and 2 and comparative steel sheets 1 and 2). The properties of each high-strength steel plate are shown in Table 1. The tensile strength was measured by taking JIS No. 5 test pieces with the longitudinal direction parallel to the rolling direction of the steel plate and conducting a tensile test in accordance with JIS Z 2241:2011.

[0082] [Manufacturing of resistance spot welded joints: set of two identical pieces] Next, resistance spot welded joints were produced by overlapping two high-strength steel plates shown in Table 1 and performing resistance spot welding on the two overlapping high-strength steel plates. "Normal" (single-stage current application) in Table 1 means that the joints were produced by a method including a step of applying pressure to the two overlapping high-strength steel plates using a pair of opposing electrodes, and a step of forming a nugget and a corona bond by applying current between the electrodes while applying pressure to the high-strength steel plates. The other production methods 1 to 4 correspond to the production methods described in this specification. Detailed production conditions are as follows:

[0083] The two steel sheets were arranged almost horizontally, and a pair of electrodes were arranged so as to sandwich the steel sheets. The electrode arranged on one steel sheet was the movable electrode, and the electrode arranged under the other steel sheet was the fixed electrode, and the upper electrode was moved toward the lower electrode to apply pressure to the steel sheets. When the current was started, the current value was instantly increased to a predetermined value, and then the current value was maintained constant until the nugget was completed. Other welding conditions are shown below. The impact angle is the angle between the axial direction of the movable electrode and the direction perpendicular to the surface of the steel sheet. The clearance is the distance between the surface of the steel sheet and the electrode, and is defined here as the distance between the tip of the lower electrode and the surface of the steel sheet before welding at the point where they are closest to each other. The impact angle and clearance are disturbance elements of resistance spot welding and are factors that cause LME cracking. The impact angle and clearance were set as follows to create conditions that make it relatively easy for LME cracking to occur. The pressure force was maintained at 4 kN for the holding time listed in Table 1 after the nugget was formed. Welding machine: Servo pressure stationary welding machine, single-phase AC (frequency 50 kHz) Electrode: Dome Radius (DR) Cr-Cu Electrode tip shape: φ6mm, R40mm Pressure during energization and holding: P: 4kN Current value I at the time when nugget formation is completed: 8kA (conditions for forming a nugget of 5.5 to 6.5 mm) Current application time (when forming the nugget): 18 cycles (360 ms) Hitting angle: 5° Clearance: 0.3mm

[0084] [Evaluation of LME crack resistance] Resistance spot welding was performed 10 times for each high-strength steel plate. The resistance spot welded joints obtained in this way were cut on a plane passing through the center of the nugget and perpendicular to the steel plate surface, and the cross section was appropriately prepared and checked for the presence or absence of cracks using an optical microscope. A test with 3 or fewer cracks out of 10 tests (number of cracks occurring out of 10 tests) was deemed to have passed, and the resistance spot welded joint was evaluated as being capable of suppressing the occurrence of LME cracks during spot welding. The results are shown in Table 1.

[0085] [Table 1]

[0086] With reference to Table 1, in Comparative Example 1, since the requirement that the hardness of the second depth region is lower than the hardness of the first and third depth regions is not satisfied, the second depth region cannot sufficiently absorb the strain introduced into the steel sheet by deformation during spot welding, which is considered to have led to an excessive increase in strain in the first depth region. As a result, it is considered that molten zinc penetrated from the surface layer of the steel sheet to the inside, and the occurrence of LME cracking could not be sufficiently suppressed. In Comparative Example 2, although the hardness of the second depth region was controlled to be lower than the hardness of the third hardness region, the requirement that the hardness of the second depth region is lower than the hardness of the first depth region is not satisfied, similarly, since the second depth region could not sufficiently absorb the strain introduced into the steel sheet by deformation during spot welding, which is considered to have led to an excessive increase in strain in the first depth region. As a result, it is considered that molten zinc penetrated from the surface layer of the steel sheet to the inside, and the occurrence of LME cracking could not be sufficiently suppressed.

[0087] In contrast, in the present invention examples 3 to 10, the hardness of the second depth region was controlled to be lower than that of the first depth region and the third depth region, so that the second depth region was able to fully absorb the strain introduced into the steel sheet due to deformation during spot welding, and it is considered that excessive increase in the strain in the first depth region was able to be suppressed. As a result, the occurrence of LME cracking was fully suppressed in all the present invention examples. In particular, in the present invention examples 4 to 7 and 10 manufactured by the manufacturing methods 1 to 3, the area ratio of the η phase in the corona bond on the overlapping surface and in the weld shoulder on the electrode side surface was 20 area % or less, so that no LME cracking was observed at all, and very high LME cracking resistance was achieved. In addition, in the present invention example 6, which was manufactured by the manufacturing method with a cooling time among the present invention examples 3 to 10, the nugget had a double structure, whereas in all the other present invention examples, the nugget had a single structure.

[0088] [Example 2] [Manufacturing of resistance spot welded joints: dissimilar 2 or 3 piece sets] In this example, two- or three-piece resistance spot welded joints were manufactured using the high-strength steel plate 2 of Example 1 and a low-strength steel plate with a tensile strength of 603 MPa in the combination shown in Table 2. Details of the manufacturing conditions are as shown in Example 1 and Table 2. Table 2 also shows whether each steel plate was zinc-based plated (galvannealed hot-dip plating). As with Example 1, the resistance spot welded joint was evaluated as passing if the number of cracks was 3 or less out of 10 tests, and was evaluated as a resistance spot welded joint that can suppress the occurrence of LME cracking during spot welding. The results are shown in Table 2.

[0089] [Table 2]

[0090] Referring to Table 2, in all of Examples 11 to 13 of the present invention, the occurrence of LME cracking was sufficiently suppressed by using high-strength steel plate 2 in which the hardness of the second depth region was lower than the hardness of the first depth region and the third depth region. [Explanation of symbols]

[0091] 1 Resistance spot welded joints 11 High strength steel plate 11' steel plate 12 Zinc-based plating 13. Nugget 14 Coronabond 15 Layered Surface 16 Heat-affected zone 17 Welding 18 Weld shoulder A electrode

Claims

1. A plurality of overlapping steel plates; a nugget for joining the steel plates, and a welded portion having a corona bond and a heat-affected zone formed around the nugget; A resistance spot welded joint comprising: At least one of the plurality of steel plates is a high-strength steel plate having a tensile strength of 980 MPa or more, The high-strength steel sheet has a zinc-based coating, or a steel sheet adjacent to the high-strength steel sheet has a zinc-based coating, On a surface of the base material of the high strength steel plate where the base material is in contact with the zinc-based plating, A resistance spot welded joint, characterized in that the hardness of a region 10 to 60 μm deep from the base metal surface is lower than the hardness of a region 1 to 10 μm deep from the base metal surface and the hardness of a region 60 μm or more deep from the base metal surface.

2. a surface of the base material of the high-strength steel plate in contact with the zinc-based plating is located at an overlapping surface of the multiple overlapping steel plates, The base material has a surface area of ​​1 to 10 μm deep and has a diameter of 10 to 200 precipitates / μm that are less than 0.1 μm. 2 exists at a number density of The resistance spot welded joint according to claim 1, characterized in that the amount of solute C in a region at a depth of 10 to 60 μm from the surface of the base material is less than 0.20 mass%.

3. 3. The resistance spot welded joint according to claim 2, characterized in that an amount of η phase of the zinc-based plating in a corona bond of the overlapping surfaces of the plurality of steel sheets where a base material surface of the high-strength steel sheet is in contact with the zinc-based plating is located is 20 area % or less.

4. a surface of the base material of the high-strength steel plate in contact with the zinc-based plating is located on the outermost surface of the multiple overlapping steel plates; The base material has a surface area of ​​1 to 10 μm deep and has a diameter of 10 to 200 precipitates / μm that are less than 0.1 μm. 2 exists at a number density of The resistance spot welded joint according to claim 1, characterized in that the amount of solute C in a region at a depth of 10 to 60 μm from the surface of the base material is less than 0.20 mass%.

5. 5. The resistance spot welded joint according to claim 4, wherein an amount of η phase in the zinc-based plating in a weld shoulder portion on the outermost surfaces of the plurality of steel plates, where a base metal surface of the high-strength steel plate is in contact with the zinc-based plating, is 20 area % or less.

6. A step of pressing the stacked steel sheets using a pair of opposing electrodes; forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; continuously decreasing the current value between the electrodes to zero while maintaining pressure on the steel plates; The method for manufacturing a resistance spot welded joint according to any one of claims 1 to 5, comprising:

7. A step of pressing the stacked steel sheets using a pair of opposing electrodes; forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; reducing the current value between the electrodes to zero while maintaining pressure on the steel plates; The current value between the electrodes at the time when the formation of the nugget is completed is defined as I, and 1 / 2 of the total sheet thickness in mm of the steel sheet is defined as tm.

6. The method for producing a resistance spot welded joint according to claim 1, wherein the current value between the electrodes is held at a constant value of 0.12×tm or more in a range of 0.9×I to 0.3×I during or within less than 0.04 seconds after the current value between the electrodes is reduced to 0.

8. A step of pressing the stacked steel sheets using a pair of opposing electrodes; A step of preheating the steel sheets by applying a pre-current between the electrodes while pressing the plurality of steel sheets; forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; The method for manufacturing a resistance spot welded joint according to any one of claims 1 to 5, comprising:

9. A step of pressing the stacked steel sheets using a pair of opposing electrodes; forming a nugget and a corona bond by applying a current between the electrodes while pressing the plurality of steel sheets; reducing a current value between the electrodes to zero while maintaining pressure on the steel plates; a step of maintaining the applied pressure at 0.8×P or more for 0.2 sec to 0.4 sec in a state where the current value between the electrodes is set to 0; The method for manufacturing a resistance spot welded joint according to any one of claims 1 to 5, wherein P is a pressing force at a time when formation of the nugget is completed.

Citation Information

Patent Citations

  • Spot welding method for high-strength steel sheet

    JP2011005544A

  • High intensity resistance-welding joint and manufacturing method thereof

    JP2014180698A

  • Spot welding method

    JP2016068142A

  • Joint structure and joint structure manufacturing method

    JP2020082102A

  • Spot welding member

    JP2020179413A